19p13.2 Microdeletion including NFIX associated with overgrowth and intellectual disability suggestive of Malan syndrome. Issue 1 (December 2016) - Dong, Hai-Yun; Zeng, Hui; Hu, Yi-Qiao; Xie, Li; Wang, Jian; Wang, Xiu-Ying; Yang, Yi-Feng; Tan, Zhi-Ping
Abstract Background Overgrowth syndromes represent clinically and genetically heterogeneous conditions characterized by a wide spectrum of malformations, tall stature, intellectual disability and/or macrocephaly. Results In a cohort of four clinically characterized patients with overgrowth syndrome without known causative gene mutation, we performed an Illumina SNP-array analysis to identify the pathogenic copy number variations. We identified two rare copy number variations harboring overgrowth syndrome related genes. Patient 1 was Malan syndrome with a 1.4 Mb 19p13.2-13.13 microdeletion includingNFIX, and Patient 2 was identified as Sotos syndrome with a 1.6 Mb 5q35.2 microdeletion encompassingNSD1 . Conclusions We identified two patients associated with Manlan syndrome and Sotos syndrome respectively. We also discuss the use of the microarrays-based candidate gene strategy in Mendelian disease-gene identification.